The transforming growth factor beta-1 in the oncogenesis of human lung adenocarcinoma - V. E. Shevchenko; I. S. Bryukhovetskiy; Z. N. Nikiforova; S. V. Kovalev; I. A. Kudryavtsev; N. E. Arnotskaya (Успехи молекулярной онкологии, 2017)
Background. The transforming growth factor beta 1 (TGF-β1) is one of the most important tissue factors secreted by the development of epithelial tumors. Increased expression of TGF-β1 in lung tumors promotes cancer cells survival enhancing their growth, migration, invasion, angiogenesis, immune system suppression.Objective: to study molecular mechanisms of TGF-β1 action on A549 human lung adenocarcinoma cells by means of proteomic high-resolution mass spectrometry. Results. Intracellular signaling pathways responsible for the involvement of TGF-β1 in the oncogenesis of non-small cell lung cancer have been found, which include the differential expressed proteins of the families of cullin, ETS oncogenes, histone diacelases, cyclin-dependent kinases, and the signaling pathway phosphatidylinositol 3-kinase (PI3K).Conclusions. Important patterns are determined that could be used for the development of new approaches for detection of lung cancer metastasis candidate markers and potential therapy targets of this decease.